Pengaruh E-Promotion, Brand Trust Dan Online Customer Review Terhadap Minat Beli Konsumen Produk Fashion Pada Marketplace Tiktok Shop - Habibburohman, Habibburohman; Widarko, Agus; Rachmadi, Kartika Rose (UNIVERSITAS ISLAM MALANG, 2024)
Abstract .This research aims to test and explain the influence of e – promotion brand trust and online customer review on customer buying interest for fashion products at the tik tiok shop marketplace. This research uses a quantitative approach which uses the maholtra formula in order to determine the sample because the population is still not known for certain. Looking at the calculation results of the calculation results of the maholtra formula, the sample size is 100. To solve the problem in this research, spss is used to analyze various types of tests. Carried outsuch as validity tests, reliability tests, normality tests, classical assumption tests, hypothesis tests, multiple linier regression tests and adjusted r2 coefficient of determination tests. The results of this research are that e – promotion, brand trust and online customer review influence both partially and simultaneously on buying interest. Keywords : E – Promotion, Brand Trust,Online Customer Review, Customer Buying Interest